Relationship Between School Types and Levels of Anxiety in a Sample of Bogotá Schoolchildren - González Salazar, Erika; Timón Guzmán, Karla; Riveros Munévar, Fernando (Pensando Psicología, 2016)
Introduction: Anxiety is a normal human response, but becomes pathological when it persists and endures over time. According to national and global studies, this is one of the disorders that has increased, apparently and more frequently affecting young people. Objectives: To determine the relationship between school types and levels of anxiety, and find differences or similarities in gender and grade, according to school type in a sample of Colombian children. Methodology: Quantitative, cross-sectional research, with a descriptive scope by comparing groups. The sample consisted of 658 schoolchildren from public and private schools between third grade of primary education and seventh grade of high school; the State-Trait Anxiety Inventory for Children (STAIC) in the version validated for Colombia was used. Results: Statistically significant differences were found in the ratings for the concern component, with higher scores on the sample of students from private schools, higher serenity scores for males and higher concern scores for females. Moreover, there are no differences in levels and types of anxiety according to school grade. Conclusions: There are higher levels of anxiety in children enrolled in private schools and higher levels of concern in school girls.